ANTIMICROBIAL ACTIVITY OF A POLYMER COMPOSITE WITH TRICLOSAN (Eurasian Journal of Ecology, 2023)
Triclosan is an antimicrobial ingredient used in many health and household products, items including plastics, textiles and food packaging materials. There are rather contradictory data regarding the antimicrobial activity of polymeric formulations with immobilized triclosan. In the present study, polymer composites containing triclosan were studied. It is illustrated that the polymer composite containing triclosan (5%) revealed a high antimicrobial effect against the S. aureus 6538-P strain, ensuring the death of 100% of bacteria in vitro. The study of material stability under the influence of several physico-chemical factors such as light, UV radiation, pH 2 and pH 8, abrasion is an important parameter for scaling up material production and commercialization. The preservation of the antimicrobial activity of the material against strains: S. aureus 6538-P; Kl. pneumoniae 10031 after 1 and 2 weeks, after 1 - 12 months of daily exposure (light, UV radiation, pH 2 and pH 8). Thus, it was found that the antimicrobial activity of the samples containing triclosan (5%) persists after a year of daily exposure to external factors that mimic conventional conditions of usage. The fungicidal activity of the composite with TCS with a surface contact time of 4 hours against strains of C. albicans 2091 and the clinical isolate of C. albicans were detected at the level of reducing the growth of bacteria by 82.1% and 92.2%, respectively. However, the polymer composite did not have antifungal activity against the C.albicans 10231 strain after 3 cycles of mechanical abrasion.Keywords Antimicrobial activity, triclosan, polymer composite, fungicidal activity.